EXPLORING THE ROLE OF APOLIPOPROTEIN A AS A PREDICTIVE BIOMARKER FOR FECAL INCONTINENCE SEVERITY IN THE ELDERLY: A FOCUS ON LIPID-IMMUNE INTERACTIONS - Wijaya, Bryan Anna; Limas, Peter Ian; Firmansyah, Yohanes; Sari, Triyana; Santoso, Alexander Halim (Prosiding Seminar Nasional COSMIC Kedokteran, 2025)
Fecal incontinence (FI) is a common problem among the elderly, affecting their quality of life. Identifying reliable biomarkers like Apolipoprotein A (Apo-A) could improve management strategies, as its anti-inflammatory properties may help predict the severity of FI. This study aims to assess Apo-A as a lipid biomarker for predicting the severity of fecal incontinence, using the Fecal Incontinence Severity Index (FISI) for measurement. This cross-sectional study involved 93 elderly participants at Bina Bhakti Nursing Home, who exhibited varying FI levels. The severity was evaluated using the FISI, while serum lipid profiles were analyzed to measure Apo-A levels. We assessed Apo-A’s predictive ability for FI severity through the area under the curve (AUC) from the receiver operating characteristic (ROC) curve. The state variable was set at 0 on the FISI scale, indicating the absence of FI. The AUC for Apo-A was found to be 0.631, with a p-value of 0.031, indicating that higher Apo-A levels are significantly linked to the absence of fecal incontinence. Apo-A is a promising biomarker for predicting FI severity, although its predictive capacity is limited. Future studies should investigate combining Apo-A with other inflammatory markers to enhance prediction accuracy.